Tractate Ketubot Sixth Order: Tahorot. Tractate Niddah - Guggenheimer, Heinrich W. (Studia Judaica, 2006)
The Tractate Ketubot ("marriage contracts") discusses inter alia the sum specified at the time of marriage to be paid in the event of divorce or the husband's death, together with the mutual obligations of man and wife, the wife's property, the law of inheritance in the female line and the widow's rights. The Tractate Nidda ("Female impurity") regulates conduct during menstruation (cf. Lev 15:19ff) and after birth (Lev 12); further topics are women's life stages, puberty and various medical questions.